The Berrybender narratives - McMurtry, Larry (McMurtry, Larry. Berrybender narratives., 2011)
A single-volume anthology of the epic story of the Berrybender pioneer family follows the relocation of British aristocrats Lord and Lady Berrybender to 1830 Texas, where their idealistic plans are shaped by their daughter's relationship with frontiersman Jim Snow.